Pendampingan Penyusunan Pembuatan Rencana Anggaran Belanja (RAB) pada Sistem Iuran Pemeliharaan Lingkungan (IPL) di Perumahan Jade Park Serpong 2 - Novita Sari, Sukarni; Aryani, Fika; Supriyadi, Endang; Sofiana, Maya; Agoestyowati, Redjeki; Wahyuni, Rita; Juardi, Juardi (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
In managing Housing Environmental Maintenance Contributions (IPL), it is necessary to create an Expenditure Budget Plan (RAB) because it forms the foundation for formulating financial strategies and schedules for housing operational activities. Errors in the Expenditure Budget Plan (RAB) can have a negative impact on the entire process, resulting in financial setbacks and activity delays, therefore it requires accurate calculations and estimator’s skills in complying with current information and standards. Community Service Activitiey (PKM) was carried out at the Jade Park Serpong 2 Housing Complex in January 2024 to February 2024, at this stage the socialization of activities was carried out to the administrators of the Jade Park Serpong 2 Community Association, besides that we also provided accompaniment in the process of preparing and making the Expenditure Budget Plan with Ms.Excel. As well as providing socialization to residents to be orderly in paying their monthly contribution obligations. In the final stage, an evaluation was carried out with discussion after the training had been completed to find out the extent of the participants’ absorption of the material they had received.